Methodology for Tendering the Performances in Long Distance Rail Passenger Transport - Gasparik, Jozef; Mesko, Pavol; Zahumenska, Zdenka (Periodica Polytechnica Transportation Engineering, 2019)
A fundamental step in the liberalisation of the rail market has been the separation of the railway infrastructure from the railway operating. The partial liberalisation of the rail market in the European Union (EU) was already underway in 2010. Opening up the market to new private railway operators means that operators can compete for the performance of selected lines. The opening up process of domestic rail passenger transport markets according to the fourth railway package has a variety of levels in Member States. This process is requested to be performed not later than 2019, while making public tenders for transport service contracts compulsory in the public interest. The paper is focused on tender implementation steps for long-distance rail passenger transport and shows the legislation requirements for the tendering process. There is a need to analyse the technical and other obstacles and threats to the operation of long-distance rail services entering competition. The idea is to meet the objectives of the EU White Paper on transport and The Regulation (EC) No 1370/2007 of the European Parliament and of the Council of 23 October 2007 on public passenger transport services by rail and by road and repealing Council Regulations (EEC) No. 1191/69 and 1107/70.